Investigating the structure-function relationships in insect cytokine-like stress-responsive peptides - Su, Andy (Kansas State University, 2024)
Insects employ a range of humoral and cellular responses to defend themselves against pathogen invasion. A family of peptides has been identified in many insects, including the tobacco hornworm, Manduca sexta, which may function as insect cytokines to regulate immune responses. They are activated at times of stress, such as pathogen invasion, wounding, and heat or cold shock. Previous structural studies reveal well-defined structures for two SRP homologs, consisting of two beta-strands and a beta-turn in the core region, with the relative stability and secondary structural features of this core region likely essential for their biological activity. The diverse roles played by the SRP family within the insect immune system make each of their structure-activity relationships intriguing. The structure of M. sexta SRP-3 (27AA) and SRP-6 (26AA), both stabilized by a disulfide bond, was investigated through 2D homo- and hetero-nuclear NMR spectroscopy. Nuclear Overhauser Effect (NOE) derived constraints were then used to calculate the lowest energy structures of SRP-3 and SRP-6.
Keywords: Stress-Responsive Peptide (SRP); Nuclear Magnetic Resonance (NMR)